The Effectiveness of Using Comic in Teaching Reading Narrative Text - Setyawan, Farid Helmi (Universitas PGRI Adi Buana Surabaya, 2018)
This study is focused on using comic as media in teaching reading at eight grade student of Junior High School in Ngawi. The problem in this study was the students‟ motivation on reading especially on narrative text was low and their score in some test was average low. They still confused to understand the content of the story, it was proved by the score on their test was average low in reading questions, it was 65,7 and they could not retell the content of the story briefly. By using the comic in teaching learning, the students are helped to understand the contents of the story that they read. The method in this study used qualitative research in the term of case study. The subject of the study was eight grade students of junior high school. The number of participant was 60 students. The result of the study showed that the implementation of teaching reading by using comic as media give benefit to students, it showed from 48 of 60 students or 80% of the students agreed the use of comic as learning media. From the questionnaire result, the comic gives benefit in teaching reading to the students‟ reading skills improvement. It revealed that 52 of 60 students or 87% of the students positively responded after the implementation activities yet only 13% of the students showed their uncertainty of its benefits. The use of comic can also be combined by other techniques in order to develop the understanding of material and make the students enjoy, interest, and enthusiasm during teaching learning process. Moreover, the result showed that comic helped students in understanding the content of the story.